Repúdio à feminilidade ou feminilidade como máscara?: um estudo psicanalítico sobre o feminino em Game of Thrones - Silva, Juliane de Oliveira (2019)
This work aims to analyze the possible meanings for the feminine from the Cersei character of the series Game of Thrones. The psychoanalytic method was used through the techniques of psychoanalytic observation, clinical diary, reading directed by listening and transferring the researcher to the text. Cersei presents herself as a masquerade, since she recovers with the representations of the Mother and the Whore. The female mask understood as a phallic sign that gives it value and acceptance in a phallocentric and patriarchal society. The mask is directly related to the Male Complex, anchored in performance, and not in the singularity and the recognition of oneself. To the extent that women use this device to establish themselves, they reinforce this same system that constitutes the feminine as depreciated. The feminine is then approached from the castrated/non-castrated dichotomy, revealing a phallic-narcissistic functioning, from horror to castration and repudiation of femininity. The psychic record of femininity confronts the phallic record, opening up primitive instinctual inscriptions which are often hidden by omnipotent defenses. The use of violence is a primitive defensive reaction to the reality of castration, whose aim is to castrated person: subjects, men and women, who attack the woman in order to destroy their own femininity. Women's experience permeates diversity, since the process of becoming a woman reveals innumerable possibilities for the exercise of womanhood. In this way, the search for female identity reveals a decentering of the subject that seeks a new way of being in the world, through the admission of femininity.